A DESCRIPTIVE STUDY OF PRACTITIONERS’ USE OF YOGA WITH YOUTH WHO HAVE EXPERIENCED TRAUMA - Nance, Madeline; Sease, Megan; Crowe, Brandi; Van Puymbroeck, Marieke; Zinzow, Heidi (International Journal of Child, Youth and Family Studies, 2022)
It is not uncommon for youth (ages 2–19) to experience trauma. There are various types of traumatic events that may lead to adverse effects on youths’ emotional, cognitive, social, physical, and spiritual health. It is important that youth receive support and resources to address the negative impacts trauma may have on their minds and bodies. Yoga is a holistic practice that may address these negative effects in all 5 health domains. However, there are many inconsistencies and gaps in the literature regarding the use of yoga with youth who have experienced trauma. The purpose of this descriptive survey research study was to address these inconsistencies by describing the approaches of 56 practitioners who utilize yoga with youth who have experienced trauma, and their perceptions of how and why they use yoga with these youth. Findings highlighted the importance of implementing trauma-specific adaptations when facilitating yoga with youth who have experienced trauma, such as increasing participant autonomy, providing a safe environment, and developing a therapeutic rapport. Results also indicated that the most common use of yoga among these practitioners was to address emotional and physical needs of youth who have experienced trauma. Implications of study findings and opportunities for future research are discussed.